2021
DOI: 10.1021/acs.inorgchem.1c00794
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytically Stable and Trifunctional Zirconium-Based Organic Frameworks toward Cr2O72– Detection, Capture, and Photoreduction

Abstract: Chromium Cr(VI) is frequently used in many fields and has been intensively researched for detection and/or removal from contaminated water. However, the existing approaches are still of low efficiency, high cost, and cumbersome in operation. It is thus highly imperative to hunt for alternative avenues to get out of the predicament. In this work, two bcu topological and highly stable zirconium-metal−organic frameworks (Zr-MOFs) of 1 and 2 have been deliberately prepared, displaying channel-type interior spaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…MOFs, comprising metal ions/clusters and organic linkers, have emerged as a kind of fastest-growing porous materials due to their high surface area, adjustable pores, and intriguing properties. As known, MOF materials are considered as an excellent platform for specific targeted functionalities, playing an important role in multifarious applications. Nevertheless, previous studies have shown that the stability of MOFs is highly demanded for the utilization of materials in water systems or even harsh conditions, which could be modified or reinforced via ingenious construction of both the organic linkers and metal nodes. For the purpose of immensely improving their stability, high-valence metals, including Fe 3+ , In 3+ , and Zr 4+ , were used for building ultrastable MOFs, such as MIL series, , PCN series, , and NU series. , Furthermore, luminescent Zr-MOFs have drawn increasing consideration and exhibited promising applications in fluorescence recognition and photocatalytic reaction because their ultrastable features originated from the strong Zr–O bonds and stable Zr 6 O clusters as well as their excellent optical properties. Until now, the limited water-tolerant MOFs like BUT-39 and JLU-MOF60 have been employed as both fluorescence sensors and photocatalysts to detect and eliminate Cr­(VI) in the water phase. Nevertheless, the development of multifunctional MOFs in practice for the sensing as well as the photoreduction of toxic Cr­(VI) is still limited, which remains an ongoing challenge. , …”
Section: Introductionmentioning
confidence: 99%
“…MOFs, comprising metal ions/clusters and organic linkers, have emerged as a kind of fastest-growing porous materials due to their high surface area, adjustable pores, and intriguing properties. As known, MOF materials are considered as an excellent platform for specific targeted functionalities, playing an important role in multifarious applications. Nevertheless, previous studies have shown that the stability of MOFs is highly demanded for the utilization of materials in water systems or even harsh conditions, which could be modified or reinforced via ingenious construction of both the organic linkers and metal nodes. For the purpose of immensely improving their stability, high-valence metals, including Fe 3+ , In 3+ , and Zr 4+ , were used for building ultrastable MOFs, such as MIL series, , PCN series, , and NU series. , Furthermore, luminescent Zr-MOFs have drawn increasing consideration and exhibited promising applications in fluorescence recognition and photocatalytic reaction because their ultrastable features originated from the strong Zr–O bonds and stable Zr 6 O clusters as well as their excellent optical properties. Until now, the limited water-tolerant MOFs like BUT-39 and JLU-MOF60 have been employed as both fluorescence sensors and photocatalysts to detect and eliminate Cr­(VI) in the water phase. Nevertheless, the development of multifunctional MOFs in practice for the sensing as well as the photoreduction of toxic Cr­(VI) is still limited, which remains an ongoing challenge. , …”
Section: Introductionmentioning
confidence: 99%
“…According to our previous work, polyhedral and colorless pristine Zr-MOF was successfully synthesized. 1 As shown in Figure 1, eight connected Zr 6 clusters were linked by L 2− to provide a bcu topological rigid network exhibiting open channels with a diameter of about 7.3 × 11.28 Å 2 along the c-axis. Compared with colorless fresh Zr-MOF, the color of in situ-synthesized RhB@Zr-MOF crystals changed to pink.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…After 60 min of photocatalysis, 16.1, 33.8, and 84.5% of Cr­(VI) was reduced respectively at pH 3, 2, and 1, indicating that the photocatalytic reduction of Cr­(VI) was an acid-catalyzed behavior . This phenomenon is consistent with other reports on Cr­(VI) reduction by MOF photocatalysts. …”
Section: Resultsmentioning
confidence: 94%
“…Metal–organic frameworks (MOFs), a class of crystalline inorganic–organic hybrid materials, have gathered particular attention in the field of photocatalysis due to their intriguing structures, powerful designability, and high surface areas. What is more exciting is that the photophysical properties of MOFs can be effectively tuned at the atomic level by virtue of abundant metal, organic secondary building units and their multiple interactions. In recent years, MOFs as heterogeneous catalysts have made notable progress in photoreduction of Cr­(VI) to Cr­(III). In general, MOF catalysts with high stability, large specific surface area, broad-band visible absorption and relative high density of catalytic active sites are pursued in Cr­(VI) photoreduction, where the assembly of high-valent metal ions (e.g., Ti 4+ , Zr 4+ and Fe 3+ ) and photoactive polycarboxylate ligands is the most popular strategy. However, MOF catalysts possess high energy barriers between metal clusters and ligands, which hinders the long-range migration of photogenerated charges in the MOF structure and further limits the photocatalytic performance of MOFs. In addition, relatively narrow apertures of MOF catalysts also limit the mass transfer rate of the substrate in channels and then restrict the promotion of catalytic efficiency. Inspired by the influence of sonochemistry for heterogeneous catalytic reactions, MOF-based photocatalytic systems with acoustic stimulation should be developed more to give scope to the advantage characteristics of MOF materials in photocatalytic reactions …”
Section: Introductionmentioning
confidence: 99%